Credit Risk Management via Capital Adequacy: Insights on Stability from Indonesia Regional Banks - Chajar Matari Fath Mala; Sapto Jumono (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the moderating role of Capital Adequacy Ratio on the relationship between Non-Performing Loans and core banking indicators Lerner Index, market share of loans, market share of deposits, technical efficiency, scale efficiency, and interest rate spread across two categories of Indonesian Regional Development Banks: undercapitalized (Category-1) and well-capitalized (Category-2). Using quarterly panel data from 24 Indonesian Regional Development Banks for the period 2012–2022 and estimated with Generalized Least Squares, the results show that Capital Adequacy Ratio significantly moderates the effect of Lerner Index, market share of deposits, and interest rate spread on Non-Performing Loans, strengthening risk absorption capacity in Category-2 banks. However, Capital Adequacy Ratio does not effectively mitigate risks arising from aggressive loan growth, particularly in Category-1 banks. Additionally, technical efficiency and scale efficiency reduce Non-Performing Loans only when capital buffers are adequate. These findings suggest that Capital Adequacy Ratio affects the risk–return trade-off differently across bank types, highlighting the importance of tailored regulatory frameworks and reinforcing the notion that capital adequacy must be supported by strong governance and operational efficiency to effectively manage credit risk.